Paragraph Alignment in Academic Writing: Theories and Practices - Pokharel, Bishnu Prasad; Sharma, Bal Krishna; Banu, Sultana (Bhairahawa Campus Journal, 2024)
The study examines the issues surrounding the arrangement of paragraphs in academic writing while focusing on the relationship between the theoretical underpinnings of academic writing and practices. It aims to familiarize beginner writers with the theory of paragraph writing and examples in academic papers. The theoretical underpinning of academic writing and the regular application of the theory among the researchers support the internal validity for them. Informed by the theory of academic writings developed by Toulmin (2003), Anderson (2007), Bailey (2011), Zinsser (2011), and Greene and Lidinsky (2015), the issue is analyzed based on qualitative research design, drawing insights and data from secondary sources. The discussion shows that the problem of paragraph arrangement is related to writers’ lack of consistent application of the theories in their writings. Based on the assumption that the base for academic writing is a paragraph, this study contends that researchers fail to structure their argument and justification in their paragraphs at the proper position to validate their logic because they lack sufficient theoretical reinforcement and practices. Arguments with warrants and evidence followed by a conclusive remark and the springboard are the prerequisites to render paragraphs sound, coherent, and organized in academic writing.